The verb ʔadʒa ‘come’ in Jordanian Arabic: three levels of grammaticalization - Abdullah A. Jaradat; Moh’d A. Al-Omari; Nisreen N. Al-Khawaldeh; Raid N. Al Hammouri (Humanities & Social Sciences Communications)
Abstract This paper investigates the grammaticalization of the verb ʔadʒa ‘come’ in Jordanian Arabic. The study argues that the verb has been grammaticalized into three meanings that constitute three levels on the grammaticalization pathway. These three meanings coexist i.e. are not considered three diachronic stages. The first meaning is to introduce a purpose clause; it is the least grammaticalized since the core lexical meaning of the verb is still apparent. The second meaning that the verb ‘come’ is grammaticalized into is intention; it is more advanced since the core lexical meaning is completely absent. The third meaning the verb come is grammaticalized into is prediction. It can be considered the most advanced since the verb come is used as a preposition meaning ‘around’. Finally, the paper provides several tests to differentiate the lexical verb from the grammaticalized forms including: the types of complements the lexical verb and gramaticalized forms require, the logical completions of the sentences, negation, and elliptical answers for yes/no questions. All of these tests show that the lexical verb and the grammaticalized forms do not require the same complements, are negated differently, and are asked about in yes/ no questions in a different manner.